A Narrative Stylistic Analysis of (Voice) in Doris Lessing’s "An Old Woman and her Cat" in Terms of Gerard Genette’s Model - Narjis Abdul-Kareem, / Majeed Hameed Jassim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The present study is an attempt to investigate Doris Lessing’s" An Old Woman and her Cat" applying Gerard Genette’s model "The Narrative Discourse Method , mainly the concept of voice with its subdivisions of (person or narrator, time of narration, level of narration). The ultimate goal of this research is to spotlight the efficiency of Genette’s theory as an analytical tool and to illustrate how this analysis enriches and enhances the readers understanding of Doris Lessing’s writing style. The researcher has found out that Genette’s model, the concept of "voice" in particular with its sub divisions is applicable to the short story "An Old Woman and her Cat" .Also, the use of narrative technique and stylistic devices contribute to the overall meaning of the short story. Moreover, the narrative choices influence the readers’ perception of characters, events, and themes within the short story.